2012
DOI: 10.1001/archinternmed.2011.1326
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Carotid Plaque Screening on Smoking Cessation and Other Cardiovascular Risk Factors

Abstract: In smokers, carotid plaque screening performed in addition to thorough smoking cessation counseling is not associated with increased rates of smoking cessation or control of cardiovascular risk factors. Trial Registration  clinicaltrials.gov Identifier: NCT00548665.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 53 publications
(77 reference statements)
2
51
0
Order By: Relevance
“…The Northern Manhattan Cohort Study, a population-based cohort study with a unique race/ethnicity profile, reported an overall carotid plaque prevalence of 57% among community-dwelling residents aged ≥39 years26. Similar prevalence rates were reported in other studies, with rates ranging from 47–58%1526272829. The San Daniele Project, a population-based asymptomatic carotid atherosclerosis study in Italy, reported a lower prevalence rate of carotid plaque (13.3% in men and 13.4% in women) in 199230.…”
Section: Discussionsupporting
confidence: 61%
“…The Northern Manhattan Cohort Study, a population-based cohort study with a unique race/ethnicity profile, reported an overall carotid plaque prevalence of 57% among community-dwelling residents aged ≥39 years26. Similar prevalence rates were reported in other studies, with rates ranging from 47–58%1526272829. The San Daniele Project, a population-based asymptomatic carotid atherosclerosis study in Italy, reported a lower prevalence rate of carotid plaque (13.3% in men and 13.4% in women) in 199230.…”
Section: Discussionsupporting
confidence: 61%
“…Expressed likelihood of behavior change should be greeted with caution in light of these limitations, especially given the existing literature on lack of behavior change in the general population in response to cardiac screening results. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Though there are no studies to support such practices, carotid ultrasound scanning for detection of increased cIMT or carotid plaque may lead to increased prescription of aspirin and statins by physicians [41] and intensified goal setting for LDL-cholesterol levels [42]. However, conflicting results have been reported regarding the impact of carotid ultrasound scanning on patient motivation [41,43]. Lipid-lowering drugs can reduce carotid plaque volume [44]; nevertheless, cIMT and plaque are biomarkers that change slowly over time, therefore patients may be on optimal medical therapy for a prolonged period of time and, yet, have increased cIMT values and/or plaques.…”
Section: Clinical Outcomesmentioning
confidence: 99%